2016
DOI: 10.1261/rna.054502.115
|View full text |Cite
|
Sign up to set email alerts
|

Cracking the epitranscriptome

Abstract: Over 100 distinct chemical modifications can be catalyzed on RNA post-synthesis, potentially serving as a post-transcriptional regulatory layer of gene expression. This review focuses on recent advances, knowledge gaps, and challenges pertaining to N6-methyladenosine (m6A), an abundant modification of mRNA for which substantial progress has been made in recent years. The discussed aspects are also very relevant for a wide range of additional modifications on mRNA collectively coined the epitranscriptome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 67 publications
0
60
0
Order By: Relevance
“…RNA modifications that previously went undetected are now known to play major roles in governing gene expression in both prokaryotic and eukaryotic organisms (Deana et al, 2008; Schwartz, 2016). For instance, recent studies have shown that adenosine methylation can stimulate translation and accelerate mRNA degradation in human cells (Wang et al, 2014; Wang et al, 2015; Meyer et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…RNA modifications that previously went undetected are now known to play major roles in governing gene expression in both prokaryotic and eukaryotic organisms (Deana et al, 2008; Schwartz, 2016). For instance, recent studies have shown that adenosine methylation can stimulate translation and accelerate mRNA degradation in human cells (Wang et al, 2014; Wang et al, 2015; Meyer et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome-wide maps have also been obtained for N 1 -methyladenosine (m 1 A) (Dominissini et al 2016), N 6 ,2 ′ -O-dimethyladenosine (m 6 Am) (Linder et al 2015;Mauer et al 2016), 5-methylcytosine (m 5 C) and pseudouridine (Y), revealing their involvement in biological processes such as stress responses (Carlile et al 2014), protein synthesis quality control (Tuorto et al 2012;Hussain et al 2013;Blanco et al 2014), and mRNA stability (Mauer et al 2016), among others. There are several excellent reviews on these few relatively well-characterized RNA modifications (Klungland and Dahl 2014;Li and Mason 2014;Frye et al 2016;Gilbert et al 2016;Li et al 2016;Schwartz 2016;Zhao et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…RNA can harbor nearly distinct 100 chemical modifications after its synthesis (44). Since their initial discovery more than 60 years ago, the vast majority of research on the modification of RNAs has focused on highly abundant RNA species, such as rRNAs, tRNAs, and snRNAs.…”
Section: Epigenetic Modificationsmentioning
confidence: 99%
“…Since their initial discovery more than 60 years ago, the vast majority of research on the modification of RNAs has focused on highly abundant RNA species, such as rRNAs, tRNAs, and snRNAs. However, the lack of sensitive methods has long hampered the characterization of RNA modifications of minimally expressed mRNAs (44). The possibility of the use of next-generation sequencing approaches has now increased the interest in RNA modifications of coding mRNAs and in their functions in normal and pathological situations.…”
Section: Epigenetic Modificationsmentioning
confidence: 99%